Pendidikan Inklusif: Tantangan dan Peluang dalam Implementasinya di Indonesia - Rida Melinda; Ahmad Suriansyah; Wahdah Refia Refianti (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
Inclusive education can provide opportunities for students with special needs to have equality in education in public schools. This research is motivated by the challenges in implementing special education in schools in terms of teacher readiness, facilities and infrastructure, and environmental factors. This study aims to identify these barriers and formulate practical solutions in realizing an inclusive learning environment. This study uses a qualitative approach with interviews, observations, and literature studies in several inclusive schools. The results of this study show that the factors that become challenges in implementing inclusive education include the lack of teachers' understanding of the concept of inclusion, limited supporting facilities, and there is a social stigma regarding children with special needs. Therefore, government and school policies are needed to overcome the challenges of implementing inclusive education.